Recovery Following Sport-Related Concussion: Integrating Pre- and Postinjury Factors Into Multidisciplinary Care. Issue 6 (November 2019) - Kontos, Anthony P.; Elbin, R. J.; Sufrinko, Alicia; Marchetti, Gregory; Holland, Cyndi L.; Collins, Michael W.
Abstract : Objective: Update concussion recovery curves by considering pre- and postinjury modifying factors. Determine whether there is a dose-response for modifying factors on recovery. Setting: Sports medicine concussion clinic. Participants: A total of 314 athletes aged 12-23 years within 7 days of a concussion enrolled between 2015 and 2018. Design: Prospective cohort study. Main Measures: Categorical recovery time defined as days from injury to full medical clearance for return to play per established criteria. Preinjury factors included age, gender, concussion history, and migraine history. Postinjury factors included loss of consciousness, posttraumatic amnesia, posttraumatic migraine symptoms, and high symptom burden. Results: Average recovery was 27.5 ± 25 days. Five factors were prognostic of recovery: (1) younger than 18 years, (2) female, (3) history of migraine, (4) posttraumatic migraine symptoms, and (5) high symptom burden ( P < .05). Recovery percentage at 21 days after injury was 96.7% for participants with 0 factor, 65.3% for those with 1 to 2, and 31.8% for those with 3 to 5—with prognostic separation in low- to high-risk groups of 62%. Conclusions: Findings support a dose-response for combined pre- and postinjury factors on recovery. Both the type and quantity of modifying factors influence recovery and should be considered in prognosis and approaches to multidisciplinary care.